2007
DOI: 10.1086/518499
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Measures of Extragalactic Sources behind the Southern Galactic Plane: New Insights into the Large‐Scale Magnetic Field of the Inner Milky Way

Abstract: We present new Faraday rotation measures ( RMs) for 148 extragalactic radio sources behind the southern Galactic plane (253 l 356 , jbj 1:5 ), and use these data in combination with published data to probe the large-scale structure of the Milky Way's magnetic field. We show that the magnitudes of these RMs oscillate with longitude in a manner that correlates with the locations of the Galactic spiral arms. The observed pattern in RMs requires the presence of at least one large-scale magnetic reversal in the fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
290
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(317 citation statements)
references
References 30 publications
25
290
0
2
Order By: Relevance
“…Using RMs of 554 southern pulsars mostly in the first and fourth Galactic quadrants, Han et al (2006) conclude that the field in the spiral arms interior to the Sun is counterclockwise (CCW) as viewed from the Galactic North Pole (a convention that we A&A 513, A65 (2010) follow), while the field in the interarm regions is most likely clockwise (CW). Brown et al (2007) used RMs of 148 EGS close to the Galactic plane (|b| ≤ 1.5 • ) in the fourth Galactic quadrant, in combination with RMs of 120 pulsars in the same region. They concluded that the best-fit model to those data has a CW field everywhere, except in the Crux-Scutum arm and in the Molecular Ring.…”
Section: Rm ∝mentioning
confidence: 99%
See 3 more Smart Citations
“…Using RMs of 554 southern pulsars mostly in the first and fourth Galactic quadrants, Han et al (2006) conclude that the field in the spiral arms interior to the Sun is counterclockwise (CCW) as viewed from the Galactic North Pole (a convention that we A&A 513, A65 (2010) follow), while the field in the interarm regions is most likely clockwise (CW). Brown et al (2007) used RMs of 148 EGS close to the Galactic plane (|b| ≤ 1.5 • ) in the fourth Galactic quadrant, in combination with RMs of 120 pulsars in the same region. They concluded that the best-fit model to those data has a CW field everywhere, except in the Crux-Scutum arm and in the Molecular Ring.…”
Section: Rm ∝mentioning
confidence: 99%
“…We used the 148 EGS observed and used by Brown et al (2007) in the Galactic longitude range 253 • ≤ l ≤ 358 • and with Galactic latitudes |b| ≤ 1.…”
Section: The Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years extensive efforts have been made to enlarge the RM samples of background sources at low Galactic latitudes (e.g. Brown et al 2007, Van Eck et al 2011. The RM data behind the Galactic disk (see Fig.1 of Han 2013) are much denser in the outer Galaxy than in the inner Galaxy.…”
Section: Magnetic Fields In the Galactic Diskmentioning
confidence: 99%